2018
DOI: 10.1002/pola.29003
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective synthesis and polymerization of Exo‐5‐trimethylsilylnorbornene

Abstract: Herein the stereoselective two‐step synthesis of pure exo‐5‐trimethylsilylnorbornene is reported. The monomer proved to be highly reactive in both metathesis and addition polymerization. ROMP polymerization was catalyzed by the first‐generation Grubbs catalyst. High‐molecular‐weight saturated addition polymers were prepared using nickel or palladium complexes as precatalysts and Na+[B(3,5‐(CF3)2C6H3)4]− and/or MAO as cocatalysts. The obtained addition polynorbornenes are highly gas permeable and microporous ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Interesting results concerning free volume distribution in a polymer were obtained from the analysis of the prepared addition polymers by positron annihilation lifetime spectroscopy (PALS). It was found that in the synthesized polyDNBD, the intensity of smaller free volume elements ( I 3 ) is significantly higher than larger ones (Table 2), in contrast to earlier studied microporous Si-containing addition polynorbornenes [21,22]. At the same time, the intensity of larger free volume elements is very low.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Interesting results concerning free volume distribution in a polymer were obtained from the analysis of the prepared addition polymers by positron annihilation lifetime spectroscopy (PALS). It was found that in the synthesized polyDNBD, the intensity of smaller free volume elements ( I 3 ) is significantly higher than larger ones (Table 2), in contrast to earlier studied microporous Si-containing addition polynorbornenes [21,22]. At the same time, the intensity of larger free volume elements is very low.…”
Section: Resultsmentioning
confidence: 61%
“…This makes polynorbornenes attractive to design new polymers with desired properties [19,20]. Earlier we have shown that Me 3 Si-substituted addition polynorbornenes, being rigid-chain linear polymers, possess BET (obtained by Brunauer-Emmett-Teller method) surface area up to 780 m 2 /g, and are promising materials for membrane gas separation of hydrocarbons or CO 2 /N 2 because of their extremely high gas permeability and/or high separation selectivities [21,22,23]. Herein we report the synthesis and properties of novel network amorphous porous polymers based on bifunctional norbornene monomers, namely norborbornadiene-2,5 and its oligomers (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…This by-product is a saturated compound and will not affect the polymerization of the prepared Si-containing exo-isomers. 26 In addition to (AllPdCl) 2 , Pd(OAc) 2 was also estimated as a source of Pd. The activity of the Pd(OAc) 2 -containing system turned out to be higher at a low temperature than that of the (AllPdCl) 2 /R-MOP catalyst, but at 75 C it becomes less active ( Table 2).…”
Section: Catalyst Bmentioning
confidence: 99%
“…Concerning the selective synthesis of Si-containing exo-norbornenes, a single example of the hydrosilylation of NBD with only an "activated" silane (trichlorosilane) has been described before. 25,26 At the same time, a selective hydrosilylation of NBD with non-activated silanes (e.g. trialkylsilanes or hydrosiloxanes) has still not been realized.…”
Section: Introductionmentioning
confidence: 99%
“…Both groups of the developed polynorbornenes are able to remove heavy hydrocarbons from natural and associated petroleum gases. Recently several new polymers from norbornene derivatives were developed as promising membrane materials [131][132][133][134][135][136][137] and unexpected relationships between structures of the polymers and their membrane properties were found. For example, some polynorbornenes with the flexible silicon-containing side groups displayed enhanced nbutane/methane selectivity (up to 50) and the metathesis polynorbornenes were revealed for the first time that are more permeable than their addition isomers [133].…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%